Comparison of clinical efficacy, immune response and postoperative adverse reactions of transurethral holmium laser lithotripsy and percutaneous nephrolithotomy in elderly patients with complex upper urinary tract renal calculi: a retrospective cohort study - Fu, Dian; Chen, Rui; Yi, Xiaoming; Wu, Ding; He, Haowei; Li, Ping; Zhou, Wenquan; Ge, Jingping; Cheng, Wen (Frontiers in Surgery, 2025)
ObjectivesThis study aimed to evaluate the clinical efficacy, immune response, and postoperative adverse effects of transurethral holmium laser lithotripsy (RIRS) vs. percutaneous nephrolithotomy (PCNL) in elderly patients with complex upper urinary tract renal calculi.MethodsA retrospective analysis was conducted on 70 elderly patients treated from January 2020 to January 2021. The control group (n = 32) underwent PCNL, while the observation group (n = 38) received transurethral holmium laser lithotripsy. Pre- and post-operative comparisons included serum creatinine (Scr), cystatin-C, kidney injury molecule-1 (KIM-1), immune indices, thyroxine (TH), and urokinase (UK). Stone clearance rates and adverse reactions were also assessed.ResultsThe observation group showed less bleeding, shorter hospital stays, higher hemoglobin decrease, and longer operation time (P < 0.05). Higher stone clearance rates were observed in the RIRS group at 86.84% and 76.32% for first and second stages, compared to 65.64% and 53.13% in the PCNL group. Postoperatively, Scr, Cys-C, and KIM-1 levels were lower in the RIRS group. Both groups exhibited decreased CD4+ and CD4+/CD8+, increased CD8+, reduced TH, and elevated UK levels post-surgery (P < 0.05). Adverse reactions were similar between groups.ConclusionsFor elderly patients with complex renal calculi, transurethral holmium laser lithotripsy offers superior stone clearance and reduced renal damage compared to PCNL, despite a longer operation time. Consideration of individual patient conditions is crucial for selecting the optimal procedure.